Straight-line conventional transient rate analysis for long homogeneous and heterogeneous reservoirs (2012)
A linear flow regime is a very important flow regime presented in fractured wells, horizontal wells and long reservoirs. Either pressure-transient analysis or rate-transient analysis may be affected by a linear flow regime. In the case the case of production rate most of the analysis is conducted by decline-curve fitting and little attention has been given to rate-transient analysis. This paper presents the governing equations used for rate-transient analysis in elongated systems and provides examples using the conventional analysis. The methodology allows for the estimation of reservoir permeability, reservoir width and geometrical skin factors. If the test is long enough, reservoir drainage area and well position inside the reservoir can also be determined. The methodology was successfully verified by its application to synthetic cases.